Sexual and Cardiovascular health.Factors Influencing on the Quality of Sexual Life of Coronary Heart Disease Patients - a Narrative Review - Piegza M; Smolarczyk J; Piegza J (Vascular Health and Risk Management)
Magdalena Piegza,1 Joanna Smolarczyk,2 Jacek Piegza3 1Department of Psychiatry, Faculty of Medical Sciences in Zabrze, Medical University of Silesia, Tarnowskie Gory, Poland; 2Department of Psychoprophylaxis, Medical University of Silesia, Tarnowskie Góry, Poland; 3Third Department of Cardiology, Faculty of Medical Sciences in Zabrze, Silesian Center for Heart Diseases, Medical University of Silesia, Zabrze, PolandCorrespondence: Joanna Smolarczyk, Email joanna.smolarczyk@sum.edu.plAbstract: Regular sexual activity is comparable to moderate exercise and may be safe for patients with cardiovascular disease (CVD). According to the recommendations of the Princeton III Conference (P3), people with a low risk of adverse cardiac events can undertake sexual activity safely, while other patients must first stabilise their cardiovascular status. Exercise testing is recommended to assess the safety of sexual activity in people with questionable or uncertain cardiac risk (P3). Patients after successful and uncomplicated treatment of myocardial infarction (MI) can return to sexual activity after 3 weeks if the stress test is negative. The 4th Princeton Conference (P4) recommends the use of the 2019 regimen developed by the American College of Cardiology (ACC) and American Heart Association (AHA) to assess the risk of atherosclerotic cardiovascular disease (ASCVD) in men with ED (ACC/AHA ASCVD 2019). Sexual health education plays an important role in the successful return to safe sexual activity, which should include post-MI patients and their relatives. The responsibility for counselling lies with cardiologists, general practitioner (GP) and nursing staff. Sexual rehabilitation should be an integral part of cardiac rehabilitation, and lifestyle modification and optimal treatment of underlying medical conditions are key to maintaining psychophysical well-being and a successful sex life.Keywords: sexual activity, cardiovascular risk factors, erectile dysfunction, Princeton consensus, myocardial infarction